Spatial variability of soil erodibility factor using geo-statistics method in Duhok dam watershed, Kurdistan region, Iraq - I, Lida; Govay, Marwan B. I.; Barwari, Vahil I. H.; Rekani, Omar A. O. (Sulaimani Journal for Pure and Applied Sciences, 2016)
Soil erosion is one of the crucial problems in watershed and environmental management. It is obvious soil and water management can reduce soil losses and land degradation. One of the important factors in universal soil loss equation (USLE) to determine rate of erosion is soil erodibility factor. It is related to intrinsic properties of the soil properties. By determining and evaluating this factor, soil erosion can be decreased to minimum amount. Traditional methods such as regression models cannot estimate precision of variables and don’t take spatial variability of soil properties. By using geo-statistical methods all changes in soil properties in distribution can be estimated with less error and high accuracy. In this research, by using 30 point of soil samples of Duhok dam watershed, the spatial variability of soil erodibility factor and some of soil properties such as percent of organic matter, particle size distribution and soil structure were obtained. Then graphical interpolation of soil properties was performed by using Kriging method. The statistical results showed that most variables had a normal distribution. Variability analysis on soil attributes according to soil erodibility, showed that exponential, spherical and linear to sill models was the most models to predict spatial variability of studied soil parameters. The Soil spatial variability pattern, is similar to silt and very fine sand pattern due to high effect of this factor on soil erodibility. According to the kriging map, soil erodibility in the east, south and north parts of the studied area is more than other parts. Soil erodibility in this location of research area based on estimation map showed need to more attention for conservation the soil and control erosion.
Keywords: Erodibility; Geostatistics; Spatial variability; Watershed